The Roles of Job Satisfaction and Perceived Supervisor Support in the Relationship between Followership Styles and Psychological Well-Being - Tuhumury, Endy; Putranta, Martinus Parnawa; Paepae, Mpholle Clement (Media Ekonomi dan Manajemen, 2023)
The quest to provide excellent services causes the aviation industry face challenges that can impair the well-being or â€œhappinessâ€ of its employees. Therefore, managing employee well-being is crucial for the industry to help its employees feel positive while serving the companies. This research aimed to examine the roles of followership styles, job satisfaction and perceived supervisor support in promoting psychological well-being in the Indonesian air transport operator contexts. Specifically, the research examined the impact of job satisfaction on psychological well-being and assessed whether job satisfaction itself was influenced by employeesâ€™ followership styles and their perceived supervisor support. A test was also performed to examine the moderating role of perceived supervisor support in the relationship between followership styles and job satisfaction. On-line questionnaires were distributed to potential respondents using a combination of convenience and purposive sampling. Â A number of 109 non-managerial employees from several Indonesian commercial and non-commercial air transport operators involved. Â Structural Equation Modeling was adopted to test the proposed hypotheses. The findings showed the majority of respondents enacted â€œexemplary followershipâ€ styles. This style positively related to job satisfaction. However, perceived supervisor support was not found to moderate the relationship. The managerial implication of the findings is outlined.